PET crystal structure regulation and control method and application thereof

The crystal structure of PET products is regulated by high-temperature isothermal crystallization method, which solves the problem of low degradation efficiency of high-crystalline PET products by biological enzymes, significantly improves the degradation efficiency, and realizes the green recycling of PET products.

CN119710935AActive Publication Date: 2025-03-28HANGZHOU NORMAL UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411893141.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Existing biological enzymes are inefficient when degrading high-crystalline PET products, and existing structural regulation methods cannot effectively improve the degradation ability of biological enzymes to the PET crystal region.

Method used

The crystal structure of PET products is regulated by high-temperature isothermal crystallization method, expand the spacing of the lamellar crystals, and more exposed the amorphous regions in the spherical crystals, thereby promoting the degradation of PET molecular chains by biological enzymes.

Benefits of technology

It significantly improves the degradation efficiency of biological enzymes on high crystallinity PET products, realizes green recycling of PET products, reduces processing costs, and conforms to the concept of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710935A_ABST
    Figure CN119710935A_ABST
Patent Text Reader

Abstract

The invention discloses a PET crystal structure regulation and control method and application thereof. The method comprises the following steps: carrying out melting treatment on a PET product to be recycled at 250 DEG C or above, and then transferring to 200-240 DEG C to crystallize for at least 1 minute. Through high-temperature isothermal crystallization, the size of an amorphous region between lamellas of a PET product to be recycled is increased, so that PET degrading enzyme can partially enter the amorphous region between the lamellas, and degradation of a part of PET molecular chain segments in spherocrystals is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a PET crystal structure control method and application thereof. Background Art

[0002] Polyethylene terephthalate (PET) is widely used in food packaging and textiles due to its excellent thermal stability, mechanical properties, chemical resistance, safety and non-toxicity. However, PET products are difficult to degrade naturally in nature, making them an important source of plastic pollution. Currently, how to efficiently recycle and reuse PET products has become a key issue that needs to be solved urgently.

[0003] As a low-energy and high-yield PET recycling strategy, bioenzymatic degradation has attracted much attention in recent years. PET degrading enzymes can act on the ester bonds in the PET molecular chain to break and depolymerize the PET chain. The recovered terephthalic acid (TPA) monomer can also be used as a polymerization monomer to resynthesize PET for recycling. At present, dozens of PET degrading enzymes have been discovered and extracted in the field of enzyme structural biology, and their degradation efficiency has been improved through genetic modification. The most active PET degrading enzyme can almost completely degrade amorphous PET within 3.3 hours.

[0004] However, existing bio-enzymes still face difficulties in degrading high-crystallinity PET products (especially those with a crystallinity higher than 20%). In order to promote the degradation efficiency of bio-enzymes on PET crystal regions, people have tried to regulate the microstructure of PET. Currently, the common structural regulation methods are as follows:

[0005] Chemical modification: Change the molecular structure of PET by introducing specific chemical groups. For example, copolymerization modification introduces flexible segments or functional groups, which can improve certain properties of PET to a certain extent. However, the chemical modification process is complicated, costly, and may affect the original excellent properties of PET, such as thermal stability and mechanical properties. In addition, the modification process may introduce new environmental problems, which is not conducive to large-scale application.

[0006] Physical blending method: blending PET with other polymers or additives. This method can adjust the performance of PET to a certain extent, but the compatibility of the blend is a major problem. If the compatibility is poor, it will lead to phase separation, making the material performance uneven, and thus affecting the overall performance of PET products. It is impossible to effectively improve the degradation ability of biological enzymes on its crystalline region.

[0007] Traditional heat treatment (such as annealing): PET products are annealed within a certain temperature range to change their crystal structure. However, the temperature range of traditional annealing is limited, and it is not aware of controlling the spacing between PET lamellae, which has little effect on improving the wetting of biological enzymes in the crystal area and cannot fully meet the needs of promoting the degradation of high-crystallinity PET biological enzymes.

[0008] In summary, the existing means of regulating the structure of PET products have many defects, and a more effective regulation method is urgently needed to improve the degradation efficiency of PET products by biological enzymes and realize the green recycling of PET products. Summary of the invention

[0009] The purpose of the present invention is to address the deficiencies of the prior art and to provide a PET crystal structure control method and application thereof.

[0010] The purpose of the present invention can be achieved by the following technical solutions: In a first aspect, the present invention provides a method for regulating the crystal structure of PET, the method comprising: The PET products to be recycled are first melt-treated at above 250°C, and then transferred to 200-240°C for crystallization for at least 1 minute.

[0011] Preferably, the method further comprises post-treating the crystallized product, wherein the post-treating comprises naturally cooling the product at room temperature.

[0012] Preferably, the melting temperature is 270° C. and the melting time is 3 minutes.

[0013] Preferably, the crystallization temperature is 230° C. and the crystallization time is 1-60 min.

[0014] Preferably, the crystallinity of the PET product is higher than 20%.

[0015] In a second aspect, the present invention provides a method for improving the efficiency of PET bioenzyme degradation, comprising: The PET product is regulated by the above method to obtain a PET product with regulated crystal structure; PET products with regulated crystal structure are used as substrates for PET bioenzymes.

[0016] The beneficial effects of the present invention are at least: The present invention proposes to expand the distance between PET flakes by high-temperature isothermal crystallization, so that the amorphous region in the spherulite is more exposed, providing more favorable conditions for enzymes to act on the PET molecular chain, and promoting the degradation of the PET molecular chain segments inside the spherulite.

[0017] The PET substrate preparation process of the present invention is relatively simple and easy to implement, and only involves conventional operation steps such as melting, isothermal crystallization and natural cooling, without the need for complex equipment and cumbersome process flow. At the same time, by accurately controlling process parameters such as melting temperature, crystallization temperature and crystallization time, effective regulation of the PET crystal structure can be achieved, with high controllability and repeatability. This makes the method easier to operate and promote in actual production and application, and is conducive to large-scale processing of PET products, improving recycling efficiency and reducing processing costs.

[0018] The method of promoting bioenzyme degradation of PET products of the present invention is helpful to realize the recycling of PET. The degradation product terephthalic acid (TPA) monomer can be used as a polymerization monomer to synthesize PET again, forming a closed-loop cycle. This not only reduces the dependence on raw petroleum resources, reduces energy consumption and carbon emissions in the PET production process, but also improves the utilization rate of resources, conforms to the concept of sustainable development, and is of great significance to promoting the development of a green circular economy in the PET industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The crystallinity data of the PET substrates prepared in the comparative example and examples 1-3 are shown.

[0020] Figure 2 The data of the size of the amorphous region between the PET substrates prepared in the comparative example and Examples 1-3 are shown.

[0021] Figure 3 The figures are comparative data of the mass ratio of spherulites of the PET substrate prepared in the comparative example and Examples 1-3 and the remaining mass ratio of the PET substrate after degradation. DETAILED DESCRIPTION

[0022] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0023] It should be noted that: In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.

[0024] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0025] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.

[0026] As can be seen from the background technology, there are many defects in the existing means of regulating the structure of PET products. Therefore, the present invention provides a more effective regulation method to improve the degradation efficiency of PET products by biological enzymes and realize the green recycling of PET products. The inventor found that semi-crystalline PET products are composed of μm-level spherulites and amorphous regions between spherulites, and the spherulites contain nm-level lamellae and amorphous regions between lamellae. In the process of biological enzyme degradation, the amorphous region between spherulites is easier to degrade, while the spherulites are difficult to degrade. This is the main reason why high-crystallinity PET products are difficult to degrade. From a molecular level, the size of the amorphous region between the biological enzyme and the PET lamellae is both at the nm level, and the size matching relationship between the two may be the key factor restricting the enzyme from degrading the PET crystalline region. Therefore, the degradation efficiency of the biological enzyme is promoted by regulating the microstructure of PET.

[0027] Therefore, on the one hand, at least one embodiment provides a method for regulating PET crystal structure, the method comprising: First, the PET product to be recycled is subjected to a high-temperature melting treatment. This step is intended to completely melt the PET product, eliminate its original crystalline structure, and provide a uniform melt state for the subsequent isothermal crystallization process. At this time, the melting temperature is above 250°C, typically but not limiting, for example, it can be 250°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C. The melting time is more than 1 minute, typically but not limiting, for example, it can be 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes.

[0028] Next, the melted PET product is quickly transferred to a high-temperature crystallization treatment. During this process, the PET molecular chains begin to rearrange and crystallize, and the spacing between the lamellae is regulated by precisely controlling the crystallization temperature and time. At this time, the crystallization temperature is 200-240°C, typically but not limiting, for example, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C. The crystallization time is more than 1 minute, typically but not limiting, for example, 1 minute, 4 minutes, 5 minutes, 16 minutes, 30 minutes, 45 minutes, 60 minutes.

[0029] In a preferred embodiment, the crystallized product is further subjected to post-treatment, wherein the post-treatment includes naturally cooling the product at room temperature, so that the PET product eventually forms a state with a specific crystal structure, thereby obtaining a PET substrate for bioenzyme degradation.

[0030] On the other hand, at least one embodiment provides a method for improving the efficiency of PET bioenzymatic degradation, comprising: The PET product is regulated by the above method to obtain a PET product with regulated crystal structure; PET products with regulated crystal structure are used as substrates for PET bioenzymes.

[0031] Some typical embodiments that embody the features and advantages of the present invention are described in detail below. It should be understood that the present invention can have many variations in different schemes without departing from the scope of the present invention. And the descriptions and illustrations therein are essentially for illustration only, not for limiting the present invention.

[0032] The PET products to be recycled used in the following examples are produced by Goodfellow Company of the United Kingdom and have a thickness of 0.25 mm.

[0033] Example 1 The PET product to be recycled is melted at 260°C for 3 minutes, then transferred to 230°C for crystallization for 4 minutes, and then naturally cooled at room temperature to obtain a PET substrate for bioenzyme degradation.

[0034] Take 10 mg of the above PET substrate, add 50 nL FAST-PETase-N212A / N277A enzyme (5 μg / mL) to form a 1 mL mixture, and place it in a 50 mM glycine, pH 9.0 buffer for degradation test, and the degradation temperature is 50 ° C. The amount of product generated is determined and analyzed by high performance liquid chromatography (HPLC) every 24 hours. The analytical column is InertSustain C18 column (4.6×250 mm, 5 μm), the mobile phase is methanol / phosphate (20 mM, pH 2.5), the flow rate is 1 mL / min, the detection wavelength is 254 nm, the elution condition is 0~15 min, and the methanol linear gradient is 35%~70%.

[0035] Example 2 The PET product to be recycled is melted at 270°C for 3 minutes, then transferred to 235°C for crystallization for 16 minutes, and then naturally cooled at room temperature to obtain a PET substrate for bioenzyme degradation.

[0036] Take 10 mg of the above PET substrate, add 50 nL FAST-PETase-N212A / N277A enzyme (5 μg / mL) to form a 1 mL mixture, and place it in a 50 mM glycine, pH 9.0 buffer for degradation test, and the degradation temperature is 50 ° C. The amount of product generated is determined and analyzed by high performance liquid chromatography (HPLC) every 24 hours. The analytical column is InertSustain C18 column (4.6×250 mm, 5 μm), the mobile phase is methanol / phosphate (20 mM, pH 2.5), the flow rate is 1 mL / min, the detection wavelength is 254 nm, the elution condition is 0~15 min, and the methanol linear gradient is 35%~70%.

[0037] Example 3 The PET product to be recycled is melted at 285°C for 3 minutes, then transferred to 240°C for crystallization for 60 minutes, and then naturally cooled at room temperature to obtain a PET substrate for bioenzyme degradation.

[0038] Take 10 mg of the above PET substrate, add 50 nL FAST-PETase-N212A / N277A enzyme (5 μg / mL) to form a 1 mL mixture, and place it in a 50 mM glycine, pH 9.0 buffer for degradation test, and the degradation temperature is 50 ° C. The amount of product generated is determined and analyzed by high performance liquid chromatography (HPLC) every 24 hours. The analytical column is InertSustain C18 column (4.6×250 mm, 5 μm), the mobile phase is methanol / phosphate (20 mM, pH 2.5), the flow rate is 1 mL / min, the detection wavelength is 254 nm, the elution condition is 0~15 min, and the methanol linear gradient is 35%~70%.

[0039] Comparative Example The PET product to be recycled is annealed at 110° C. for 24 hours and then cooled naturally at room temperature to obtain a PET substrate for bioenzyme degradation.

[0040] Take 10 mg of the above PET substrate, add 50 nL FAST-PETase-N212A / N277A enzyme (5 μg / mL) to form a 1 mL mixture, and place it in a 50 mM glycine, pH 9.0 buffer for degradation test, and the degradation temperature is 50 ° C. The amount of product generated is determined and analyzed by high performance liquid chromatography (HPLC) every 24 hours. The analytical column is InertSustain C18 column (4.6×250 mm, 5 μm), the mobile phase is methanol / phosphate (20 mM, pH 2.5), the flow rate is 1 mL / min, the detection wavelength is 254 nm, the elution condition is 0~15 min, and the methanol linear gradient is 35%~70%.

[0041] By comparing various data of Examples 1-3 with those of the comparative example during the degradation process, such as the change in crystallinity, the change in the size of the amorphous region between the lamellae, the change in the mass ratio of the spherulites, and the remaining mass ratio of the PET substrate after the degradation is completed (such as Figure 1-3 As shown in the figure, it can be clearly seen that the method of the present invention has a significant effect in promoting the degradation of PET products by biological enzymes. The cold crystallized sample (comparative example) has a crystallinity higher than 20% ( Figure 1 ) and smaller amorphous region size between lamellae ( Figure 2 ), the remaining mass ratio of the PET substrate after degradation is much larger than the mass ratio of the internal spherulites ( Figure 3 ), indicating that the degradation enzyme cannot enter the spherulites to achieve degradation; while the high temperature isothermal crystallization samples (Examples 1-3) have a crystallinity higher than 20% ( Figure 1 ), due to its significantly increased amorphous region size between lamellae ( Figure 2 ), after the degradation, the remaining mass ratio of the PET substrate is still less than the mass ratio of the spherulites ( Figure 3 ), indicating that the degradation enzyme can enter the spherulite to degrade the amorphous region. Therefore, the isothermal crystallization treatment method of the present invention can effectively regulate the PET crystal structure, improve the infiltration ability of the biological enzyme in the crystal region, and thus significantly improve the biological enzyme degradation efficiency of high-crystallinity PET products, providing a more advantageous solution for the recycling of PET products.

[0042] In summary, the present invention increases the size of the amorphous region between the lamellae of the PET product to be recycled from ~6nm to ~12nm by isothermal crystallization at a high temperature of 200~240°C, so that the PET degrading enzyme with a size of about 5nm can partially enter the amorphous region between the lamellae and achieve the degradation of a part of the PET molecular chain segments inside the spherulites. This method reveals the "size matching" mechanism of the biological enzyme infiltration inside the spherulites, and can therefore guide the further promotion of the research on the biological enzyme degradation method of PET products.

[0043] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for regulating PET crystal structure, characterized in that: The method comprises: The PET products to be recycled are first melt-treated at above 250°C, and then transferred to 200-240°C for crystallization for at least 1 minute.

2. The method according to claim 1, characterized in that: The method further comprises post-treating the product after the crystallization, wherein the post-treating comprises naturally cooling the product at room temperature.

3. The method according to claim 1, characterized in that: The melting temperature is 270° C. and the melting time is 3 minutes.

4. The method according to claim 1, characterized in that: The crystallization temperature is 230° C., and the crystallization time is 1-60 min.

5. The method according to claim 1, characterized in that: The crystallinity of the PET product is higher than 20%.

6. A method for improving the efficiency of PET bioenzyme degradation, characterized in that: The method comprises: The PET product is regulated by the method according to any one of claims 1 to 5 to obtain a PET product with regulated crystal structure; and the PET product with regulated crystal structure is used as a substrate for PET bioenzyme.

Citation Information

Patent Citations

  • PET nucleating crystallization heat treatment method

    CN103496049A

  • Method for improving thickness of polypropylene lamella through annealing treatment

    CN104610648A

  • Method for efficiently biodegrading crystalline plastics

    CN107236147A

  • Method for controlling spherulitic radial relative growth rate of iP-1-B by blending iP-1-B with LDPE

    CN108264692A

  • Method for improving enzyme degradation efficiency of waste PET bottles

    CN112480472A